Accuracy assessment of atlas L-band GNSS global correction service and autonomous positioning at Perlis, Malaysia / Mohd Zainee Zainal ... [et al.] - Zainal, Mohd Zainee; Wan Mohd Suhaimi, Wan Muhammad Syafiq; Mohd Zaki, Nurul Ain; Ghazali, Noorzalianee; Zainuddin, Khairulazhar (UiTM Press, 2021)
Differential Global Navigation Satellite System (DGNSS) is the most common positioning method used for navigation in the hydrography field. During the loss of the correction signal, the differential solution becomes an autonomous solution that may affect the accuracy of the position during that time. However, the availability of the Atlas L-band global correction service that adapts the Real-Time Precise Point Positioning (RT-PPP) technique has broadened the choice of solutions that can be used for navigation in the maritime industry and may solve the problem of signal loss. This research compares the positioning between autonomous solution GNSS and Atlas L-band correction solution using the static method to assess the accuracy of positioning between both methods. Data acquisition of the autonomous positioning and Atlas L-band service was conducted by using Hemisphere receiver VS330 and antenna A43. The statistical T-test reveals that the accuracy of analysis Atlas-L band and autonomous solution GNSS using static positioning was significant, as the p < 0.05 with 95% confidence interval. Besides, the result also shows that the position given by the Atlas L-band is more accurate and precise than Autonomous Solution GNSS, with an average position of 0.479 meters and 2.281 meters, respectively. Ultimately, the continuity of positioning data given by the Atlas L-band in the northern part of Malaysia is good, and positioning using Atlas L-band can be classified as Special Order based on the classification table by the International Hydrographic Organisation (IHO).